White list: An administrative tool to contrast crime - Amelia Barletta; Carlo Capuano; Alessandro De Iudicibus (Games, 2022)
White Lists are lists of firms set up at each Italian prefecture. It is a relatively young instrument born as an experimental project designed to solve problems for particular conditions of crime and corruption in the Italian territory. This work aims to understand if the "White List" tool can represent a reliable legality tool for the contracting station and representation for firms registered in these lists, an incentive to obtain awards for faster times of public procurement. Through a descriptive survey, we will try to photograph the "White List" phenomenon by comparing firms belonging to these lists with companies not belonging to them but which are similar in terms of size and economic sector. The comparison takes off some differences in the financial structure of the two groups of companies. in particular, the White List's firms show a better profitability and a lower recourse to third-party capital.
Keywords: 330; mafia infiltration; organised crime; White List